Thermographic evaluation and adaptation to the prosthesis of people with lower limb amputation: a qualitative approach - Luz, Soraia Cristina Tonon da; Silva, Amanda Reinert; Honório, Gesilani Júlia da Silva; Santos, Kadine Priscila Bender dos; Branco, Ruy Luiz Lorenzetti; Ruy, Tayla Siqueira (Acta Fisiátrica, 2018)
Objective: To evaluate qualitatively the characteristics of the thermographic map of the lower limb intact limb and adaptation to the prosthesis of amputated patients of lower limbs. Method: Qualitative research, descriptive and exploratory. The sample consisted of five amputees of lower limbs of both sexes, with transtibial and transfemoral levels, aged between 18 and 65 years, literate and protected by the Unified Health System (SUS). Anamnesis and thermographic evaluation were performed qualitatively analyzing the intact limb and stump applied to the Prothesis Evaluation Questionnaire (PEQ) questionnaire. Results: Thermographic images of transfemoral individuals presented in the residual limb an increase in temperature in the inguinal region, and may be due to the friction of the superior fit of the prosthesis. In all samples, temperature was observed in the lower extremity of the stump, indicating a possible reduction of vascularization in this region. In the PEQ, the domain most strongly cited as unfavorable for the participants was mobility, mainly in the questions of going up and down stairs, climbing and descending steep hills and walking on slippery places. The transpiration within the socket and the swelling of the residual limb were also complaints well cited by the participants. Conclusion: The issues of greatest impact to the adaptation of the prosthesis were the mobility, transfer characteristics related to the edema, sensation of weight and thermal discomfort of the residual limb in the region of the prosthetic fitting. Thermography showed higher values of intact limb temperature, as well as temperature increase in the prosthesis fitting region and temperature reduction at the end of the stump.